Asset allocation and Regulation 28 - Mjebeza, Athenkosi (Department of Finance and Tax, 2016)
This paper aims to determine the impact Regulation 28 has on optimal asset allocation. The revised Regulation 28 of the pensions fund act came into effect as of 1 July 2011 which imposed certain restrictions or constraints on pension funds under direct control of trustees. This study evaluates some of the constraints imposed on the Regulation 28 through the use of Markowitz (1952) efficient frontier framework and a non-parametric model. With offshore allocation increased to 25% and an additional 5% to African (ex SA) markets the study also explores the diversification prospects to international, emerging and African (exSA) markets. The findings suggest that international markets bring about increase benefits to South African markets; however, when the Regulation 28 constraint is imposed the benefits slightly diminishes. Further analysis show that emerging and African markets bring little to no benefits to optimal South African pension fund allocation. Locally, the study looked at the gold index and the findings suggest that the gold asset class increases the welfare of an investor and it's a safe haven asset class.